CO2 laser in the diagnostics of resection margins in breast tumors - A. I. Berishvili; T. M. Kochoyan; A. K. Dmitriev; A. N. Konovalov; V. A. Ulyanov; А. G. Kedrova (Опухоли женской репродуктивной системы, 2020)
To diagnostics of the evaporation of tumor tissue by radiation of single-mode medical CO2 laser is proposed a laser Doppler diagnostic method based on autodyne detection (reception on a laser resonator) of backscattered radiation from the evaporation zone. Intraoperative diagnostics of laser tissue evaporation lets surgeon to determine in real time tumour margins and evaporate it without additional normal tissue traumatization. The sensitivity limits of the method were studied on samples of malignant and benign tumors of breast together with plots of healthy tissue in vitro. It was shown that areas of tumor tissue are well determined by the autodyne method in 80 % of cases.